Effects of high oil corn and fat level on growth performance of nursery pigs - Bergstrom, J.R.; Samland, C.J.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two studies were conducted to evaluate the effects of adding high oil corn to nursery diets as compared to other sources of fat. The results of both studies suggest that addition of fat to the nursery pig diet, regardless of the source, has no significant influence on growth performance until late in the nursery phase.
Keywords: Swine; Weanling pigs; High oil corn; Fat source